Regular Domination in Various Fuzzy Graphs. Issue 1 (June 2021) - Prabakaran, P.; Vinoth Kumar, N.; Preethi, N.
Abstract: In this work, we describe regular domination set (RDS) and regular dominating number λ R (G) in FG and study some charateristics and bounds of regular domination number in several FG's.